Fibronectins containing extradomain A or B enhance osteoblast differentiation via distinct integrins - Sens-Albert, Carla; Huck, Katrin; Wabnitz, Guido H.; Nakchbandi, Inaam (The journal of biological chemistry, 2017)
Fibronectin is a multidomain protein secreted by various cell types. It forms a network of fibers within the extracellular matrix and impacts intracellular processes by binding to various molecules, primarily integrin receptors on the cells. Both the presence of several isoforms and the ability of the various domains and isoforms to bind to a variety of integrins result in a wide range of effects. In vivo findings suggest that fibronectin isoforms produced by the osteoblasts enhance their differentiation. Here we report that the isoform characterized by the presence of extradomain A activates α4β1 integrin and augments osteoblast differentiation. In addition, the isoform containing extradomain B enhances the binding of fibronectin through the RGD sequence to β3-containing integrin, resulting in increased mineralization by and differentiation of osteoblasts. Our study thus reveals novel functions for two fibronectin isoforms and the mediating receptors in osteoblast differentiation.